The importance of zakat distribution and urban-rural poverty incidence among Muallaf (new convert) - Fuadah Johari; Muhammad Ridhwan Ab. Aziz; Nursilah Ahmad; Mohd Ali A.F. (Canadian Center of Science and Education, 2024)
This study demonstrates literately the importance of regional (urban-rural) differences and the impact of zakat distribution towards the poverty alleviations among asnaf Muallaf. This study was motivated by the monthly official zakat distribution towards asnaf Muallaf that did not differentiate the true urban-rural cost of living differences. Differences in urban and rural poverty lines that did not reflect the actual urban-rural cost of living differences will provide a misleading picture of the distributional impact of development, which usually involves urban sector expansion. In a dualistic economy, one of the ways the poor benefit from development is through expansion of job opportunities in the modern predominantly urban sector, in addition to increases in productivity in the traditional predominantly rural sector. Thus, this study aims to identify the dispersal of Muallaf in terms of urban-rural poverty that involved in allocation of zakat distribution. In defining poverty between urban and rural areas, therefore, one should ensure the differences in the cost of living between these two areas. The finding suggest that, a huge of amount of zakat been allocated to the development of asnaf Muallaf in the state of Selangor especially in urban area. However, most of zakat distribution on Muallaf goes to urban region which higher in cost of living without considering a set of prices including a broader bundle of goods and services representative of the purchases of consumers in different region. Canadian Center of Science and Education.